The Communication Experience of Blind Writers (Phenomenology Study at the Library of Braille Publishing House Abiyoso Bandung) - Junaidin Junaidin; Irham Irham (2021)
The aim of this study is to know and to understand the communication experience of blind writers in the aspect of reading and writing activity. The communication experience of blind readers and writers is a process about deep reading and writing activities, whether they read braille books orwrite some inspirational works. This awareness resulted from the willingness as well as the ability to practice of reading and writing either as a physical or as a psychological experience. The method used in this study is qualitative method with a phenomenological approach. Data collection used several techniques such as observation, depth interviews and documentation. The techniques were suitable for exploring and examining the communication experiences of blind readers and writers. This study found that the experiences among blind people communications in reading and writing activities are actually combinations of physical and psychological experiences.